Category of «connecting processes» in quality management - H. S. Hasanov; L. V. Skulskaya (Омский научный вестник: Серия "Общество. История. Современность")
The quality management system is still an under-research area. This article provides an understanding of the «connecting processes» category for the further development of the theory and the practice of the quality management. A business organization must continuously create and improve the types and the forms of the communication, the management decisions and the balance. This is achieved through their continuous sequence. The work identifies the main criteria and parameters of the quality, the requirements and the conditions for the quality ensuring of the linking processes, identifies the key management indicators in the implementation of the linking processes